Frontiersman : Daniel Boone and the making of America - Brown, Meredith Mason, 1940- (Southern biography series., 2008)
Supported with copious maps, illustrations, endnotes, and a detailed chronology of Boone's life, Frontiersman provides a fresh and accurate rendering of a man most people know only as a folk hero--and of the nation that has mythologized him for over two centuries.